High-temperature-resistant insulating ceramic column for calcium carbide furnace and preparation method thereof
Patent Information
- Application Number
- CN202611250289.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-30
AI Technical Summary
综上所述,现有技术的核心问题在于:要么材料导电存在安全隐患;要么绝缘结构复杂、界面可靠性差;要么均质陶瓷材料无法协同优化导热、耐磨、抗热震等矛盾性能,难以满足电石炉日益苛刻的工况要求
1、采用多尺度复合梯度功能材料经整体成型获得单一整体构件,各区域之间为连续过渡且无物理界面,从根本上避免了现有技术中导电陶瓷本体与绝缘胶填充的拼接结构因热膨胀系数不匹配而产生的微裂纹、剥离等界面失效问题,使料柱在长期高温热循环下的绝缘可靠性和结构完整性得到根本保障。
Smart Images

Figure CN123002848A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of calcium carbide furnace technology, specifically to a high-temperature resistant insulating ceramic column for calcium carbide furnaces and its preparation method. Background Technology
[0002] The feed column of a calcium carbide furnace is a key and vulnerable component in calcium carbide production, operating for extended periods in extreme environments characterized by high temperatures, abrasion, chemical corrosion, and thermal shock. Existing technologies primarily focus on two main areas: metallic and ceramic materials, but both have significant drawbacks.
[0003] I. Fundamental Defects of Metal Feeding Columns: Currently, the feeding columns of domestic calcium carbide furnaces are almost all made of metal. The electrical conductivity of metal means that during production, if the insulation fails and leakage occurs, strong electromagnetic eddy currents will be generated within the column, causing it to heat up instantly, turn red-hot, or even melt. This not only poses a significant safety hazard but also results in enormous energy consumption. This has prompted the industry to seek alternative insulation materials.
[0004] II. Structural and Technological Defects of Early Composite Ceramic Pillars: One existing technical solution attempts to solve the insulation problem through a composite structure. The process involves: first, fabricating a conductive ceramic body based on silicon carbide and creating insulating gaps; then, filling the gaps with high-temperature resistant insulating adhesive; and finally, soldering the leads and preparing the insulating filler. This design has serious problems: First, the structure is complex, and the process steps are cumbersome (cutting, polishing, filling, welding, pressing and sintering), resulting in low production efficiency; second, under high-temperature thermal cycling, the interface between the ceramic body and the insulating adhesive, two different materials, is prone to micro-cracks or peeling due to the mismatch in their coefficients of thermal expansion, leading to insulation failure and poor reliability.
[0005] III. Performance Bottlenecks of Homogeneous Ceramic Materials: While using ceramic materials is the right direction, new high-temperature insulating ceramic feed columns have already been put into use, with operating temperatures reaching 1850℃ and offering safety and energy-saving advantages due to their non-conductive and non-magnetic properties. However, single or simply mixed ceramic refractory materials cannot simultaneously meet all the high-performance requirements of calcium carbide furnace feed columns, including extremely high temperature resistance, wear resistance, chemical stability, thermal shock resistance, and good mechanical strength. The ceramic materials used in the feed tubes disclosed in utility model CN204630383U, such as MgO, Al2O3, ZrO2, and SiC, cannot simultaneously achieve all the aforementioned properties when used individually. Even with composite formulations, such as homogeneous materials composed of ceramic matrix, Bi / Ni-supported ZrO2 nano-amorphous powder, Ta-Ce-mullite composite porous particles, and special sintering aids, the performance is uniform within the material, making it impossible to optimize for different working conditions in different parts of the feed column (such as the high-temperature core and the wear-prone surface), resulting in performance waste or localized shortcomings.
[0006] IV. The Industry's Urgent Need for High-Performance New Materials: The calcium carbide industry is accelerating its green transformation and upgrading through equipment upgrades and the introduction of new materials. Given the high-temperature characteristics of calcium carbide production, the market urgently needs new material solutions that can extend equipment lifespan and improve safety and energy efficiency. Existing ceramic feedstocks still have room for improvement in terms of fracture toughness, thermal shock fatigue life, and overall stability under extreme furnace conditions. In summary, the core problems with existing technologies are: either the material's electrical conductivity poses a safety hazard; or the insulation structure is complex and the interface reliability is poor; or homogeneous ceramic materials cannot synergistically optimize contradictory properties such as thermal conductivity, wear resistance, and thermal shock resistance, making it difficult to meet the increasingly demanding operating requirements of calcium carbide furnaces. Summary of the Invention
[0007] In order to overcome the shortcomings of the prior art, the purpose of this invention is to provide a high-temperature resistant insulating ceramic column for calcium carbide furnaces that has a stable structure, reliable performance, and long service life.
[0008] The technical solution adopted in this invention is as follows: A high-temperature resistant insulating ceramic column for calcium carbide furnaces is a single integral component obtained by integral molding of multi-scale composite gradient functional materials. Its interior is composed of a core region, a transition region and a surface wear-resistant region. The multi-scale composite gradient functional material uses silicon nitride and sialon as ceramic matrices and contains nanoscale modifiers and micron-scale reinforcing particles. The content of the high thermal conductivity phase in the core region is higher than that in the wear-resistant surface region, the content of the hard wear-resistant reinforcing phase in the wear-resistant surface region is higher than that in the core region, and the nanoscale modifier is diffusely distributed at the grain boundaries of the ceramic matrix.
[0009] Working principle: During operation, the core of the calcium carbide furnace's charging column primarily bears the high-temperature heat load—molten calcium carbide continuously erodes through the charging channel, conducting heat from the inside out; while its outer surface (especially the parts in contact with the material) mainly bears the erosion and chemical corrosion from the material. These two operating conditions place drastically different demands on material properties: the core requires high thermal conductivity to quickly dissipate heat and prevent localized overheating; the surface layer requires high hardness and high wear resistance to resist material abrasion.
[0010] This invention utilizes graded functional materials design, controlling the distribution of different functional phases during the molding process to enrich AlN whiskers (high thermal conductivity phase) in the core and SiC / B4C (hard and wear-resistant phase) on the surface, achieving synergistic optimization of "core heat dissipation and surface wear resistance". Nanoscale Bi / Ni-supported ZrO2 amorphous particles, due to their extremely small size (5-10 nm), possess high surface energy and interfacial activity. During sintering, they tend to segregate at grain boundaries, inhibiting abnormal grain growth through the Zener pinning effect. Furthermore, when cracks propagate to the grain boundaries, they absorb energy at the crack tip through stress-induced phase transformation (t-ZrO2 to m-ZrO2), resulting in a phase transformation toughening effect. Ta-Ce-mullite composite porous particles (1-5 μm) act as "obstacles" in the crack propagation path due to their micron-sized size and porous structure, forcing the crack to detour (crack deflection) or consume more energy when passing through the particles (crack bridging). The two-scale enhancement mechanisms work together to improve fracture toughness.
[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. A single integral component is obtained by integral molding of multi-scale composite gradient functional materials. The regions are continuously transitioned and there is no physical interface. This fundamentally avoids the interface failure problems such as microcracks and peeling caused by the mismatch of thermal expansion coefficients in the splicing structure of conductive ceramic body and insulating glue filler in the existing technology. This fundamentally ensures the insulation reliability and structural integrity of the material column under long-term high temperature thermal cycling.
[0012] 2. The ceramic materials based on silicon nitride and silane have high volume resistivity, which makes the material column have the characteristics of body insulation. This eliminates the safety hazard of the metal material column heating and melting due to electromagnetic eddy currents caused by the damage of the insulation device, and at the same time eliminates the loss of eddy current power.
[0013] 3. The core area is enriched with a high thermal conductivity phase to achieve efficient heat dissipation, while the wear-resistant surface area is enriched with a hard reinforcing phase to improve wear resistance, so that different parts of the same component can obtain the optimal performance configuration for their respective working conditions.
[0014] 4. Nanoscale modifiers are dispersed at grain boundaries, playing a role in pinning cracks and refining grains; micron-scale reinforcing particles dissipate fracture energy through crack deflection and bridging mechanisms. The combination of nanoscale and micron-scale components produces a synergistic toughening effect, enabling the material to simultaneously achieve high strength and good fracture toughness.
[0015] In a preferred embodiment of the present invention, the high thermal conductivity phase is aluminum nitride whiskers, and the hard wear-resistant reinforcing phase is at least one of silicon carbide micro powder or boron carbide micro powder. The nanoscale modifier is a Bi / Ni supported ZrO2 nanocrystalline powder with an average particle size of 5-10 nm. The micron-sized reinforcing particles are Ta-Ce-mullite composite porous particles with an average particle size of 1–5 μm.
[0016] Working principle: AlN is a covalent compound with a hexagonal wurtzite crystal structure and a large mean free path of phonons, resulting in extremely high thermal conductivity. When introduced in whisker form (large aspect ratio), it can form a penetrating thermally conductive network in the matrix, allowing heat to be conducted rapidly along the whisker axis, which is more efficient than granular thermally conductive phases of equal volume fraction. The extremely high hardness of SiC and B4C stems from the high bond energy of their covalent bonds and their dense atomic arrangement. When subjected to abrasive erosion, the hard particles can act as an "anti-wear skeleton" to resist the cutting and grooving action of the abrasive. Enriching the surface of these two materials in the form of micro-powder is equivalent to constructing a continuously distributed hard "armor layer" on the material surface, significantly improving the resistance to abrasive wear. The "loaded" structure of Bi / Ni supported ZrO2 nano-amorphous powder means that Bi and Ni elements are attached to the surface of ZrO2 particles in the form of nanoclusters. During sintering, Ni can react with Si3N4 in the matrix to form a small amount of low-melting-point phase, promoting particle rearrangement and densification; Bi tends to agglomerate at grain boundaries, acting as a "lubricant" for grain boundary sliding, thus improving the material's thermal shock resistance while maintaining strength. ZrO2 itself has phase transformation toughening properties, undergoing a t→m martensitic phase transformation under the tensile stress field at the crack tip, accompanied by approximately 4-5% volume expansion, producing a compressive stress shielding effect on the crack tip; in Ta-Ce-mullite composite porous particles, mullite (3Al2O3·2SiO2) itself has a low coefficient of thermal expansion and good thermal shock resistance; the introduction of Ta (tantalum) can improve the high-temperature stability of the particles; Ce (cerium), as a rare earth element, can react with impurity ions in the matrix (such as Ca²⁺) + Mg² + The reaction forms a stable second phase, purifying the grain boundaries, while Ce... 4+ / Ce³ + The variable valence property helps to suppress the crystal transformation of ZrO2 at high temperatures and stabilize its toughening effect.
[0017] Beneficial effects: 1. AlN whiskers have extremely high theoretical thermal conductivity (approximately 320 W / m·K) and are excellent electrical insulators. They can improve the heat dissipation capacity of the core without compromising the insulation performance of the material, thus meeting the dual requirements of rapid heat dissipation and safe insulation.
[0018] 2. SiC (Mohs hardness 9.5) and B4C (Mohs hardness above 9.3), as some of the hardest ceramic materials, are enriched in the wear-resistant area of the surface in the form of micro powder, which can greatly improve the wear resistance of the surface and effectively resist the high-speed erosion of calcium carbide materials.
[0019] 3. Bi / Ni supported ZrO2 nano-amorphous powder has a metastable structure and releases high interfacial energy during sintering, which promotes interfacial wetting and bonding with the matrix. At the same time, the Bi / Ni supported elements can form micro-liquid phases at the grain boundaries, further promoting densification.
[0020] 4. The porous structure of Ta-Ce-mullite composite porous particles not only reduces the elastic modulus of the particles, which is beneficial to alleviate thermal stress, but also the pores can passivate the crack tip when the crack propagates. At the same time, Ce element has the effect of stabilizing the ZrO2 phase structure.
[0021] In a preferred embodiment of the present invention, the core region accounts for 40-60% of the total volume of the ceramic column, the transition region accounts for 20-30% of the total volume, and the wear-resistant surface region accounts for 20-30% of the total volume.
[0022] Working Principle: For the feed column of a calcium carbide furnace, the core needs a sufficiently large volume to accommodate the heat-conducting network. If the core area is less than 40%, the amount of AlN whiskers added is insufficient to form a through-type heat-conducting channel, and the heat dissipation effect will be greatly reduced. However, if it exceeds 60%, there will be insufficient space left for the surface wear-resistant layer, which will affect the service life. Similarly, the surface wear-resistant layer needs to be thick enough to withstand long-term wear—the erosion of calcium carbide material is a continuous consumption process. If the surface layer thickness is insufficient (<20%), once the wear-resistant layer is worn through, the softer core material inside will be quickly exposed to the wear environment, leading to rapid failure of the feed column. If it exceeds 30%, excessive residual stress may be generated due to the large difference in performance between the surface and the core. A transition area of 20-30% ensures that the changes in composition and thermal expansion coefficient from the core to the surface are sufficiently gradual. According to the principle of thermoelasticity, the presence of a gradient transition layer changes the thermal stress distribution curve from a step-like type to a continuous type, and the peak stress is significantly reduced.
[0023] Beneficial effects: 1. The core area accounts for 40-60% of the total volume, ensuring that a sufficient volume fraction of high thermal conductivity channels can effectively dissipate heat from the furnace and prevent heat accumulation in the core; the wear-resistant surface area accounts for 20-30%, providing sufficient wear allowance to extend service life, while avoiding excessive thickness that would lead to increased costs or thermal stress.
[0024] 2. The 20-30% transition region ensures a smooth transition of composition and performance from the core to the surface, avoiding the risk of thermal stress concentration and cracking caused by sudden performance changes, and allowing the advantages of graded functional materials to be fully utilized.
[0025] In a preferred embodiment of the present invention, a reinforcing skeleton is further provided inside the ceramic column. The reinforcing skeleton is any one of heat-resistant metal wire mesh, ceramic fiber braid, or three-dimensional interconnected porous ceramic skeleton. The reinforcing skeleton and the multi-scale composite gradient functional material are metallurgically bonded or mechanically interlocked through sintering.
[0026] Working Principle: Ceramic materials are inherently brittle, exhibiting brittle fracture and lacking the plastic deformation capabilities of metallic materials. The presence of an internal reinforcing skeleton introduces a second-phase toughening mechanism: when a crack propagates within the ceramic matrix to the skeleton interface, the fracture toughness of the skeleton (metal mesh or ceramic fiber) is far superior to that of the ceramic matrix, potentially "blocking" the crack from directly penetrating. For the crack to bypass the skeleton and continue propagating, it requires additional energy (crack deflection toughening) or necessitates fiber pull-out / mesh breakage (pull-out toughening, fracture bridging toughening). The combined effect of these toughening mechanisms far exceeds the self-toughening capacity of a single material. The metallurgical or mechanical bonding interface formed through high-temperature sintering ensures that the interface does not become a weak point—if the interface bonding is too weak, the skeleton can become a source of crack initiation. This invention achieves a strong bond through co-sintering, allowing the load to be effectively transferred from the matrix to the skeleton through the interface, achieving true composite reinforcement.
[0027] Beneficial effects: 1. The pre-embedded reinforcing skeleton is equivalent to the steel bars in the ceramic matrix. When the ceramic material is subjected to impact or thermal shock, the skeleton can bridge cracks and share the load, effectively preventing the material column from undergoing brittle overall fracture and greatly improving its resistance to accidental impact.
[0028] 2. The skeleton and the ceramic matrix are sintered at high temperature to form a metallurgical bond or mechanical interlock, resulting in high interfacial bonding strength and ensuring effective load transfer between the matrix and the skeleton.
[0029] This invention also provides a method for preparing a high-temperature resistant insulating ceramic column for a calcium carbide furnace as described above, comprising: S1: Silicon nitride powder, silane powder, nano-scale modifier, micron-scale reinforcing particles and sintering aid are mixed to prepare a matrix powder; a high thermal conductivity phase is added to the matrix powder to obtain a first slurry; a hard wear-resistant reinforcing phase is added to the matrix powder to obtain a second slurry; S2: First, the first slurry is injected into the bottom of the mold to form the core material layer. Then, while continuously injecting the first slurry, the mixing ratio of the second slurry is gradually increased to form a transition layer. Finally, the second slurry is injected until the mold is filled to form a surface wear-resistant layer. After in-situ curing, the mold is demolded and dried to obtain a green body with a component gradient distribution. S3: The green body is placed in a protective atmosphere furnace, heated to 1500°C and held at that temperature under a protective atmosphere, then heated to 1750-1850°C and sintered under a pressure of 1-5 MPa. After cooling, the ceramic column is obtained.
[0030] Working Principle: The key to the integral molding of gradient functional materials achieved by the preparation process of this invention lies in the combination of "layered grouting and gel solidification": In the grouting stage, by controlling the injection sequence and mixing ratio of two different grouts, a non-uniform distribution of components is established in space; at this time, the grout is still in a liquid state, and the suspended particles tend to settle. If ordinary drying methods are used to remove the solvent, gravity settling will destroy the established gradient. This invention utilizes the cross-linking reaction of polyvinyl alcohol modified ammonium alginate gel (the carboxyl groups in ammonium alginate and the hydroxyl groups in polyvinyl alcohol form a three-dimensional network structure through hydrogen bonding or esterification reaction), so that the entire system can be "frozen" into a gel state at room temperature, the particles are locked by the network, and the gradient is precisely preserved. In the sintering stage, the stepwise heating strategy is crucial: the role of the 1500℃ low temperature range is to allow the decomposition products of organic matter (ammonium alginate) in the sintering aid to form a low-melting-point liquid phase with the alkali metal / alkaline earth metal oxides in the modified illite powder, initiating preliminary particle rearrangement; at this temperature, grain growth is not yet significant, and chemical diffusion at the gradient interface is limited. When the temperature is raised to 1750–1850℃ and a gas pressure of 1–5 MPa is applied, the amount of liquid phase increases and the viscosity decreases. Under pressure, the particle rearrangement and dissolution-precipitation process are accelerated, achieving densification close to the theoretical density. At the same time, the high-pressure nitrogen / argon atmosphere effectively suppresses the decomposition and volatilization of Si3N4 at high temperatures (Si3N4 will significantly decompose into Si and N2 at temperatures above 1800℃ under pressureless conditions), protecting the integrity of the matrix material.
[0031] Beneficial effects: 1. By dynamically adjusting the ratio of the first grout to the second grout during the grouting process, the gradient green body can be constructed in one go, without the need for complex multi-layer pressing or multiple pouring. The process is simple and highly controllable.
[0032] 2. In-situ curing is achieved by utilizing the gel crosslinking reaction in the slurry system, which allows the green body to obtain sufficient strength while maintaining the unchanged component gradient distribution, thus preventing gradient attenuation caused by particle sedimentation during subsequent demolding and drying.
[0033] 3. First, low-temperature heat preservation is used to fully remove organic matter and perform preliminary sintering. Then, high-temperature and high-pressure sintering is used to achieve complete densification. At the same time, the diffusion between gradient layers is moderately controlled, which ensures dense metallurgical bonding between layers and avoids excessive diffusion that would cause the gradient to disappear completely.
[0034] 3. The three-step process is interconnected, forming a complete process chain from powder preparation, gradient construction, and sintering densification. The resulting product has a clear gradient structure and excellent performance. In a preferred embodiment of the present invention, in step S1: The matrix powder comprises, by weight: 60-75 parts silicon nitride powder, 5-10 parts silane powder, 0.5-2 parts nano-level modifier, 2-5 parts micron-level reinforcing particles, and 5-15 parts sintering aid. The first slurry is made by adding 5 to 15 parts by weight of aluminum nitride whiskers as a high thermal conductivity phase to the matrix powder. The second slurry is made by adding 8 to 18 parts by weight of silicon carbide micro powder or boron carbide micro powder as a hard and wear-resistant reinforcing phase on the basis of the matrix powder.
[0035] Working principle: The quantitative range of each component in the formula is derived from extensive experimental optimization, reflecting the principle of "appropriate excess": if the amount of AlN whiskers added is less than 5 parts, a continuous thermally conductive network cannot be formed; if it exceeds 15 parts, the difference in thermal expansion coefficients between AlN and Si3N4 will be too large (AlN: 4.5×10). -6 / K, Si3N4: 3.2×10 -6 / K) However, excessive residual stress is generated during the cooling process, and the viscosity of the slurry increases sharply due to the high aspect ratio of the whiskers, resulting in poor fluidity. If the amount of SiC / B4C added is less than 8 parts, the surface hardness is not significantly improved; if it exceeds 18 parts, the fracture toughness of the material will decrease significantly due to the formation of a continuous skeleton between the hard phases, and sintering densification will become difficult.
[0036] In a preferred embodiment of the present invention, the aluminum nitride whiskers have a length of 5–20 μm and a diameter of 0.5–2 μm; The average particle size of the silicon carbide micro powder or boron carbide micro powder is 0.5–2 μm; The sintering aid is composed of modified illite powder and polyvinyl alcohol modified ammonium alginate gel in a mass ratio of 1:0.5 to 2. In step S1, each slurry is placed in a ball mill and wet-milled at 200-400 rpm for 4-8 hours, and the solid content of the slurry is controlled at 40-60%.
[0037] Working Principle: The aspect ratio (length / diameter) of AlN whiskers is crucial to their strengthening effect in the matrix. A larger aspect ratio results in more whisker ends and surfaces per unit volume, providing more interfacial debonding and pull-out work during crack propagation, leading to a more significant toughening effect. Simultaneously, whiskers with a large aspect ratio are more likely to overlap, reducing the thermal conductivity percolation threshold. The particle size of SiC / B4C micropowder is balanced between 0.5 and 2 μm—too fine (nanoscale) leads to agglomeration and increased slurry viscosity, while excessively rapid grain growth during sintering reduces hardness; too coarse (>5 μm) results in insufficient sintering activity and decreased interfacial bonding strength with the matrix. Modified illite powder is a layered silicate mineral containing K. + Na + Ca² + Alkali metal / alkaline earth metal ions can react with the SiO2 oxide layer on the surface of Si3N4 at high temperatures to form a low-melting-point silicate liquid phase, promoting particle rearrangement and dissolution-precipitation mass transfer. Meanwhile, the carbonaceous network remaining after the ammonium alginate gel is pyrolyzed at 300–500℃ is oxidized into CO / CO2 and escapes during subsequent high-temperature sintering. The remaining micropores are closed under pressure, without compromising the final density.
[0038] Beneficial effects: 1. AlN whiskers are 5–20 μm long and 0.5–2 μm in diameter, with a high aspect ratio (2.5–40), which can more effectively overlap in the matrix to form a thermally conductive network, while also exerting the toughening effect of fiber pull-out.
[0039] 2. The SiC / B4C micro powder has a particle size of 0.5-2μm and good sintering activity. It can achieve good bonding with the matrix at conventional sintering temperatures while maintaining the intrinsic hardness of the hard phase.
[0040] 3. Modified illite powder and polyvinyl alcohol modified ammonium alginate gel are used in combination. The organic gel builds a network to lock the gradient in the low temperature section, while the mineral components in illite promote liquid phase sintering in the high temperature section, playing the role of low temperature shaping and high temperature sintering aid.
[0041] 4. Wet ball milling at 200-400 rpm for 4-8 hours, with a solid content of 40-60%, takes into account both dispersion efficiency and slurry flowability, ensuring that each component is uniformly dispersed at the molecular level in the slurry.
[0042] In a preferred embodiment of the present invention, in step S2: The core material layer accounts for 40-60% of the total mold volume, the surface wear-resistant layer accounts for 20-30% of the thickness, and the transition layer accounts for 20-30% of the thickness. During the grouting process, vibrations with a frequency of 20–50 Hz and an amplitude of 0.1–0.5 mm are applied to achieve in-situ composition gradient construction by utilizing the difference in settling rates of particles with different densities. The in-situ curing is performed by allowing the material to stand in a constant temperature and humidity environment for 2 to 6 hours. The drying process employs a gradient heating method: first, maintain the temperature at 60°C for 2 hours, then raise the temperature to 110°C and maintain it for 4 hours, and finally raise the temperature to 150°C and maintain it for 2 hours.
[0043] Working Principle: The 20-50Hz low-frequency vibration applied during the grouting process serves two purposes: firstly, it maintains the fluidity of the grout, preventing grouting difficulties caused by premature solidification due to the gel reaction; secondly, the AlN whisker density (3.26 g / cm³) and SiC particle density (3.21 g / cm³) are both lower than Si3N4 (3.44 g / cm³), resulting in differences in the settling velocity of particles with different densities in the vibration field. This invention injects the core grout (first grout, rich in AlN) into the bottom of the mold first, followed by a surface grout (second grout, rich in SiC) with a slightly higher density. Under vibration conditions, the heavier SiC particles tend to migrate downwards, while the lighter AlN whiskers tend to float or remain suspended. However, because the gel reaction occurs gradually over 2-6 hours, the system viscosity continuously increases, and the particle migration distance is limited, preventing complete homogenization of the gradient. Instead, a controlled compositional gradient is formed, creating the gradient distribution pattern required by this invention.
[0044] The principle of gradient drying lies in the fact that water exists in different forms in the green body (free water can evaporate in large quantities at 60℃, bound water requires above 100℃, and structural water requires even higher temperatures). If high-temperature drying is used from the beginning, the surface moisture evaporates rapidly, forming a dense "hard shell," while the diffusion of internal moisture outward is hindered, resulting in high-pressure steam inside and causing cracking. However, by gradually increasing the temperature from 60℃ to 110℃ to 150℃, the moisture evaporates gradually from the surface to the inside, and the shrinkage process occurs simultaneously, avoiding destructive stress.
[0045] Beneficial effects: 1. By utilizing the difference in settling rates of particles with different densities in gravitational and vibrational fields (AlN density 3.26 g / cm³ and SiC density 3.21 g / cm³ are both lower than Si3N4 density 3.44 g / cm³, exhibiting different settling / suspension behaviors in slurry), a composition gradient is formed in situ with the assistance of mechanical vibration, without the need for complex external field equipment.
[0046] 2. Allow to cure under constant temperature and humidity for 2-6 hours to avoid uneven shrinkage and cracks caused by rapid curing, and to ensure the integrity and uniformity of the gradient green body.
[0047] 3. Gradual temperature increase drying at 60℃, 110℃, and 150℃ gradually removes free water, bound water, and organic decomposition products, effectively preventing shrinkage stress and cracking caused by rapid moisture evaporation in the green body.
[0048] In a preferred embodiment of the present invention, in step S3: The temperature is increased to 1500℃ at a rate of 5-10℃ / min and held for 1 hour; then the temperature is increased to 1750-1850℃ at a rate of 3-5℃ / min and sintered at 1-5MPa pressure for 2-4 hours. After sintering, the furnace is cooled to below 200°C before being removed from the furnace. The protective atmosphere is flowing nitrogen or argon.
[0049] Working Principle: The heating rate is crucial for preserving the gradient structure. If the heating is too rapid (e.g., >15℃ / min), temporary temperature differences will occur between layers due to variations in thermal conductivity, leading to excessive internal thermal stress and cracking in the green body. Simultaneously, if the heating is too rapid at high temperatures, the differences in interlayer chemical potential will accelerate interdiffusion, causing the originally fine gradient distribution to flatten or even disappear. This invention employs a two-stage heating process: first, a rapid (5-10℃ / min) rise to 1500℃ to complete pre-sintering and remove organic matter; then, a slow (3-5℃ / min) rise to the final sintering temperature. This is precisely to control the diffusion process during the densification stage.
[0050] The theoretical basis for applying a pressure of 1–5 MPa comes from sintering kinetics: the pressure increases the stress at the contact points between particles, accelerating diffusion creep and particle rearrangement, allowing densification to be completed at a lower temperature. This method achieves (1) avoiding excessively high temperatures leading to Si3N4 decomposition (decomposition intensifies above 1850℃); and (2) suppressing abnormal grain growth. According to the classic Coble creep model, the applied pressure P reduces the surface energy driving force required for densification, allowing for a higher relative density at the same temperature. The necessity of a protective atmosphere (N2 or Ar) lies in the fact that Si3N4 exists in decomposition equilibrium at high temperatures (Si3N4(s)). 3Si(l)+2N2(g)), the flowing N2 atmosphere increases the N2 partial pressure in the system, effectively suppressing the decomposition reaction; for AlN, its oxidation resistance is weak, and the presence of O2 will cause the formation of an Al2O3 layer on its surface, which will damage the thermal conductivity of the whiskers.
[0051] Beneficial effects: 1. Heating rates of 5–10℃ / min and 3–5℃ / min ensure heating efficiency while avoiding thermal stress cracking and excessive diffusion at the gradient interface caused by excessively rapid heating.
[0052] 2. Gas pressure of 1-5 MPa significantly reduces sintering temperature and shortens holding time, promoting densification while inhibiting excessive grain growth and maintaining the grain boundary distribution and fine-grained structure of the nano-modifier.
[0053] 3. Flowing nitrogen or argon gas protection prevents Si3N4 and AlN from oxidizing at high temperatures, ensuring that the high-temperature performance of the material is not degraded.
[0054] In a preferred embodiment of the present invention, if the ceramic column includes a reinforcing skeleton, the reinforcing skeleton is pre-positioned and fixed in the central area of the mold before slurry injection, and then slurry injection is performed so that the reinforcing skeleton is embedded inside the green body.
[0055] Working Principle: The method of introducing the reinforcing skeleton directly affects its reinforcing efficiency. This invention adopts a "pre-embedded method" rather than a "post-placed method," fixing the skeleton in the center of the mold before grouting. During grouting, the grout naturally wets and coats all the filament / fiber surfaces of the skeleton. After gel solidification, the skeleton is firmly locked inside the green body. During the subsequent sintering process, the ceramic matrix shrinks and wraps around the skeleton, forming a thermally bonded mechanical interlock. The shrinkage rate of ceramic during cooling (approximately 1-2%) is greater than that of metal skeletons (approximately 0.5-1%). This difference in shrinkage generates a certain compressive stress at the interface, which helps with interfacial bonding. Simultaneously, for ceramic fiber woven skeletons, the fiber surface may undergo an interfacial reaction with the matrix at high temperatures to form a reaction layer (e.g., Si3N4 reacts with SiO2 in the fiber to generate intermediate phases such as Si2N2O), achieving true chemical bonding. The three-dimensional interconnected structure of the skeleton ensures that it plays a toughening role in all three spatial directions. Regardless of the direction from which cracks propagate, they will be blocked or deflected by the skeleton. Beneficial effects: 1. The reinforcing skeleton is pre-positioned and fixed in the center of the mold before grouting. During the grouting process, the ceramic material naturally fills the gaps in the skeleton and solidifies in situ around it, realizing the integrated composite of the reinforcing skeleton and the ceramic matrix without the need for secondary processing or assembly.
[0056] 2. Pre-fixing ensures the skeleton is in the optimal reinforcement position inside the material column, preventing skeleton displacement or deformation during grouting and ensuring it performs the expected reinforcement and toughening effect during service. Attached Figure Description
[0057] Figure 1 This is a flowchart illustrating the steps of a method for preparing a high-temperature resistant insulating ceramic column for a calcium carbide furnace according to the present invention. Detailed Implementation
[0058] Typical embodiments embodying the features and advantages of the present invention will be specifically described in the following description. It should be understood that the present invention can have various variations in different embodiments without departing from the scope of the present invention, and the descriptions and illustrations herein are for illustrative purposes only and not intended to limit the present invention.
[0059] In the description of this application, the terms "first", "second", etc. are used only for the convenience of describing this application and simplifying the description, and are not intended to indicate or imply that the structure referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.
[0060] Example 1 See Figure 1 As shown in the figure, this embodiment discloses a method for preparing a high-temperature resistant insulating ceramic column for a calcium carbide furnace, including the following steps: Step S1 (Preparation of multi-scale composite powder slurry): By weight, 68 parts of silicon nitride (Si3N4) powder and 8 parts of Sialon powder were used as the main ceramic matrix materials. 1.5 parts of Bi / Ni supported ZrO2 nano-amorphous powder with an average particle size of 8 nm were added as nano-scale modifiers. 4 parts of Ta-Ce-mullite composite porous particles with an average particle size of 3 μm were added as micron-scale reinforcing particles. 10 parts of a sintering aid composed of modified illite powder and polyvinyl alcohol modified ammonium alginate gel in a mass ratio of 1:1 were added. An appropriate amount of anhydrous ethanol was added as a dispersion medium.
[0061] Divide the above mixed powder into two base materials: First slurry (core material): 12 parts by weight of aluminum nitride (AlN) whiskers (12 μm in length and 1 μm in diameter) are added to the above basic mixed powder as a high thermal conductivity phase. The mixed powder is placed in a planetary ball mill and wet-milled at 300 rpm for 6 hours to obtain the first slurry, with the solid content of the slurry controlled at 50%.
[0062] Second slurry (surface wear-resistant material): 15 parts by weight of silicon carbide (SiC) micro powder (average particle size 1.2 μm) are added to the above basic mixed powder as a hard wear-resistant reinforcing phase. The second slurry is prepared by the same ball milling process.
[0063] Step S2 (gradient construction of green body): A release agent is uniformly coated on the inner surface of the cylindrical material column forming mold. This embodiment does not include an internal reinforcing skeleton.
[0064] First, the first slurry is slowly injected into the bottom of the mold through a single-channel injection system, with the injection volume accounting for 50% of the total volume of the mold, forming the core material layer.
[0065] Subsequently, a dual-channel grouting system was activated. While continuously injecting the first grout, the mixing ratio of the second grout was gradually increased to form a transition layer, the thickness of which accounted for 25% of the total thickness. Throughout the grouting process, continuous slight vibrations with a frequency of 30 Hz and an amplitude of 0.3 mm were applied to the mold. Utilizing the difference in settling rates between AlN whiskers (density approximately 3.26 g / cm³, relatively low and easily suspended) and SiC particles (density approximately 3.21 g / cm³, relatively high and easily settled), a compositional gradient was constructed in situ in synergistic manner.
[0066] Finally, switch to injecting only the second slurry until the mold is full, as a surface wear-resistant layer, with a thickness of 25%.
[0067] After the grouting is completed, the mold is moved to a constant temperature and humidity chamber (temperature 25±2℃, relative humidity ≥90%) and left to stand for 4 hours. The cross-linking effect of polyvinyl alcohol modified ammonium alginate gel is used to solidify the grout in situ and lock the gradient distribution of components. Then the mold is demolded to obtain the green body.
[0068] The green blanks are placed in a forced-air drying oven and dried using a gradient heating method: first, they are kept at 60℃ for 2 hours, then heated to 110℃ for 4 hours, and finally heated to 150℃ for 2 hours to completely remove moisture and residual volatile organic compounds.
[0069] Step S3 (High-temperature sintering densification): The dried gradient green body is placed in a gas pressure sintering furnace, and after evacuation, a flow of high-purity nitrogen gas (purity ≥99.999%) is introduced as a protective atmosphere.
[0070] Sintering was carried out according to the following sintering regime: the temperature was increased to 1500℃ at a rate of 7℃ / min and held for 1 hour; then the temperature was increased to 1800℃ at a rate of 4℃ / min and held for 3 hours under a pressure of 3MPa.
[0071] After sintering, the material is slowly cooled to below 200°C in the furnace before being removed from the furnace, thus obtaining the finished high-temperature resistant insulating ceramic column for calcium carbide furnaces.
[0072] Example 2 The difference between this embodiment and Embodiment 1 is that the raw material ratio and process parameters adopt the upper limit of the range of the proposed scheme, as detailed below: By weight, 75 parts of silicon nitride powder and 10 parts of silane powder were taken as the main matrix materials, 2 parts of Bi / Ni supported ZrO2 nano-amorphous powder with an average particle size of 5 nm were added, 5 parts of Ta-Ce-mullite composite porous particles with an average particle size of 2 μm were added, and 15 parts of sintering aid composed of modified illite powder and polyvinyl alcohol modified ammonium alginate gel in a mass ratio of 1:1.8 were added.
[0073] The first slurry contains an additional 15 parts by weight of aluminum nitride whiskers (5 μm in length and 0.5 μm in diameter); the second slurry contains an additional 18 parts by weight of boron carbide (B4C) micro powder (average particle size 0.8 μm) as a wear-resistant reinforcing phase.
[0074] The ball milling process is as follows: wet ball milling at 200 rpm for 8 hours, with a slurry solid content of 60%.
[0075] During gradient construction, the core layer accounts for 60% of the total mold volume, the transition layer accounts for 20%, and the surface wear-resistant layer accounts for 20%. A vibration frequency of 50Hz and an amplitude of 0.5mm are applied.
[0076] Curing time is 6 hours. Drying is carried out using the same gradient temperature regime.
[0077] The sintering process is as follows: the temperature is increased to 1500℃ at a rate of 10℃ / min and held for 1 hour; then the temperature is increased to 1850℃ at a rate of 5℃ / min and sintered at 5MPa pressure for 4 hours. The protective atmosphere is flowing argon.
[0078] The remaining operations are the same as in Example 1, resulting in the ceramic column of this example.
[0079] Example 3 The difference between this embodiment and Embodiment 1 is that the raw material ratio and process parameters adopt the lower limit of the scheme range, and it includes an internal reinforcing skeleton, as detailed below: By weight, 60 parts of silicon nitride powder and 5 parts of silane powder were used as the matrix material. 0.5 parts of Bi / Ni supported ZrO2 nano-amorphous powder with an average particle size of 10 nm were added. 2 parts of Ta-Ce-mullite composite porous particles with an average particle size of 5 μm were added. 5 parts of sintering aid composed of modified illite powder and polyvinyl alcohol modified ammonium alginate gel in a mass ratio of 1:0.5 were added.
[0080] Five parts by weight of aluminum nitride whiskers (20 μm in length and 2 μm in diameter) were added to the first slurry; eight parts by weight of silicon carbide micro powder (2 μm in average particle size) were added to the second slurry as a wear-resistant reinforcing phase.
[0081] The ball milling process is as follows: wet ball milling at 400 rpm for 4 hours, with a slurry solid content of 40%.
[0082] Before gradient construction, the three-dimensional interconnected silicon carbide ceramic fiber braid (reinforcing skeleton) is pre-positioned and fixed in the central area of the mold, followed by grouting. The core layer accounts for 40% of the total mold volume, the transition layer accounts for 30%, and the surface wear-resistant layer accounts for 30%. A vibration frequency of 20Hz and an amplitude of 0.1mm are applied.
[0083] Curing time: 2 hours.
[0084] The sintering process is as follows: heat up to 1500℃ at 5℃ / min and hold for 1 hour; then heat up to 1750℃ at 3℃ / min and hold for 2 hours under 1MPa pressure.
[0085] The remaining operations are the same as in Example 1, resulting in a ceramic column containing an internal reinforcing skeleton.
[0086] Comparative Example 1 The following preparation method was used to prepare a commercially available homogeneous silicon nitride-bonded silicon carbide ceramic column: 70 parts silicon nitride powder, 20 parts silicon carbide micro powder, and 10 parts sintering aid (yttrium oxide + alumina) were mixed by wet ball milling for 6 hours, spray granulation, and then dry pressing (forming pressure 150 MPa). The resulting green body was sintered at 1800℃ under normal pressure for 3 hours in a nitrogen atmosphere and then cooled in the furnace. A homogeneous Si3N4-SiC ceramic column was obtained.
[0087] Following the approach outlined in CN204630383U, a homogeneous MgO-Al2O3-ZrO2 composite ceramic was prepared: 30 parts of MgO powder, 45 parts of Al2O3 powder, 20 parts of ZrO2 powder, and 5 parts of sintering aid were mixed by ball milling, spray granulation, and then isostatically pressed at 150 MPa. The mixture was then sintered at 1650℃ in air under normal pressure for 2 hours to obtain a homogeneous MgO-based composite ceramic column.
[0088] The testing method is as follows: The ceramic columns obtained in Examples 1-3 and Comparative Examples 1-2 were sampled and their performance tested according to the following standards: Bulk density and apparent porosity: determined according to GB / T 25995; Bending strength at room temperature: determined according to GB / T 6569 (three-point bending method); High-temperature flexural strength (1400℃): determined according to GB / T 14390; Fracture toughness (single-sided notched beam method): determined according to GB / T 23806; Volume resistivity (1000℃): determined according to GB / T 31838.3; Thermal conductivity (core sampling): determined according to GB / T 22588 (laser flare method); Wear volume: determined according to ASTM C704 (sandblasting abrasion test method), with the sample taken from the surface area; Thermal shock resistance: Tested according to YB / T 376.1 (held at 1100℃ for 20 min and then water-cooled and quenched, cycled 5 times), and characterized by the retention rate of residual bending strength.
[0089] The test results of each embodiment and comparative example are summarized in Table 1.
[0090] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-2.
[0091] Results Analysis In terms of mechanical properties: The room temperature flexural strengths of Examples 1-3 reached 685 MPa, 720 MPa, and 635 MPa, respectively, and the fracture toughness reached 7.8, 8.3, and 7.1 MPa·m¹ / ², respectively, all significantly better than Comparative Example 1 (520 MPa / 5.5) and Comparative Example 2 (210 MPa / 3.2). This indicates that the pinning effect of nanoscale Bi / Ni-supported ZrO2 amorphous particles at the grain boundaries and the passivation and deflection effect of micron-sized Ta-Ce-mullite porous particles on the crack tip produced a synergistic toughening effect, and the multi-scale composite mechanism effectively improved the fracture resistance of the material.
[0092] Regarding the synergy of thermal conductivity and heat dissipation: The core thermal conductivity of Example 1 is 58 W / m·K, while that of Example 2 is as high as 68 W / m·K, compared to only 35 W / m·K for Comparative Example 1 and only 12 W / m·K for Comparative Example 2. The AlN whiskers enriched in the core of this invention successfully construct a continuous and highly efficient thermally conductive network, which can rapidly dissipate the high temperature inside the calcium carbide furnace, significantly reducing the heat load on the core. This is also an important reason why the high-temperature bending strength of the examples is far superior to that of the comparative examples.
[0093] Regarding wear resistance: The surface wear volume of Example 1 was 0.8 cm³, Example 2 was only 0.5 cm³, while Comparative Example 1 was 2.5 cm³ and Comparative Example 2 was 4.8 cm³. The surface gradient enrichment of SiC / B4C micro powder significantly improved surface hardness and wear resistance, while the high density (apparent porosity ≤1.2%) further prevented the intrusion and exfoliation of abrasive media.
[0094] Regarding insulation reliability: Example 1 still exhibits a volume resistivity as high as 2.1 × 10¹² Ω·cm at a high temperature of 1000℃, while Examples 2 and 3 also maintain a resistivity on the order of 10¹² Ω·cm, whereas Comparative Example 1 is only on the order of 10¹² Ω·cm. 0 The magnitude, compared to only 10 in comparison. 8 The ceramic material of this invention is an excellent high-temperature insulator, which completely eliminates the safety hazard of metal columns heating and melting due to electromagnetic eddy currents from the material itself. At the same time, it also fundamentally avoids the leakage failure problem caused by interface moisture absorption and thermal mismatch cracking in the "conductive ceramic + insulating adhesive" splicing structure.
[0095] Regarding thermal shock resistance and durability: Example 1 achieved a strength retention rate of 92% after 5 cycles of 1100℃-water cooling thermal shock, while Example 2 achieved 95%, significantly higher than Comparative Example 1's 78% and Comparative Example 2's 55%. This is attributed to the gradient functional design eliminating the abrupt performance interface within the material, effectively mitigating thermal stress concentration. Simultaneously, the pinning effect of the nano-modifier on microcracks inhibits the propagation of thermal shock cracks, enabling the charge column to withstand the harsh conditions of frequent start-ups and shutdowns of the calcium carbide furnace and drastic temperature fluctuations.
[0096] As can be seen from the comparison of the above embodiments and comparative examples, the present invention, through the integrated design of "multi-scale composite gradient functional materials," successfully achieves synergistic optimization among multiple conflicting properties of the ceramic feed column in a calcium carbide furnace, including efficient heat conduction in the core, high hardness and wear resistance of the surface layer, high overall strength and toughness, and high-temperature insulation. Adopting the technical solution of the present invention can significantly extend the service life of the feed column, improve the safety and stability of the calcium carbide furnace operation, and reduce energy waste and maintenance costs caused by eddy current losses and frequent replacements, demonstrating good industrial application prospects and promotional value.
[0097] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.
Claims
1. A high-temperature resistant insulating ceramic feed column for a calcium carbide furnace, characterized in that: The high-temperature resistant insulating ceramic column for the calcium carbide furnace is a single integral component obtained by integral molding of multi-scale composite gradient functional materials. Its interior consists of a core region, a transition region, and a surface wear-resistant region. The multi-scale composite gradient functional material uses silicon nitride and silane as ceramic matrices and contains nanoscale modifiers and micron-scale reinforcing particles. The content of the high thermal conductivity phase in the core region is higher than that in the wear-resistant surface region, the content of the hard wear-resistant reinforcing phase in the wear-resistant surface region is higher than that in the core region, and the nanoscale modifier is diffusely distributed at the grain boundaries of the ceramic matrix.
2. The high-temperature resistant insulating ceramic column for calcium carbide furnaces according to claim 1, characterized in that: The high thermal conductivity phase is aluminum nitride whiskers, and the hard wear-resistant reinforcing phase is at least one of silicon carbide micro powder or boron carbide micro powder. The nanoscale modifier is a Bi / Ni supported ZrO2 nanocrystalline powder with an average particle size of 5-10 nm. The micron-sized reinforcing particles are Ta-Ce-mullite composite porous particles with an average particle size of 1–5 μm.
3. The high-temperature resistant insulating ceramic column for calcium carbide furnaces according to claim 2, characterized in that: The core region accounts for 40-60% of the total volume of the ceramic column, the transition region accounts for 20-30% of the total volume, and the wear-resistant surface region accounts for 20-30% of the total volume.
4. The high-temperature resistant insulating ceramic column for calcium carbide furnaces according to claim 3, characterized in that: The ceramic column is also provided with a reinforcing skeleton, which is any one of heat-resistant metal wire mesh, ceramic fiber braid, or three-dimensional interconnected porous ceramic skeleton. The reinforcing skeleton and the multi-scale composite gradient functional material are sintered to form a metallurgical bond or mechanical interlock.
5. A method for preparing a high-temperature resistant insulating ceramic column for a calcium carbide furnace as described in any one of claims 1 to 4, characterized in that, Includes the following steps, S1: Silicon nitride powder, silane powder, nano-scale modifier, micron-scale reinforcing particles and sintering aid are mixed to prepare a matrix powder; a high thermal conductivity phase is added to the matrix powder to obtain a first slurry; a hard wear-resistant reinforcing phase is added to the matrix powder to obtain a second slurry; S2: First, the first slurry is injected into the bottom of the mold to form the core material layer. Then, while continuously injecting the first slurry, the mixing ratio of the second slurry is gradually increased to form a transition layer. Finally, the second slurry is injected until the mold is filled to form a surface wear-resistant layer. After in-situ curing, the mold is demolded and dried to obtain a green body with a component gradient distribution. S3: The green body is placed in a protective atmosphere furnace, heated to 1500°C and held at that temperature under a protective atmosphere, then heated to 1750-1850°C and sintered under a pressure of 1-5 MPa. After cooling, the ceramic column is obtained.
6. The preparation method according to claim 5, wherein in step S1: The matrix powder comprises, by weight: 60-75 parts silicon nitride powder, 5-10 parts silane powder, 0.5-2 parts nano-level modifier, 2-5 parts micron-level reinforcing particles, and 5-15 parts sintering aid. The first slurry is made by adding 5 to 15 parts by weight of aluminum nitride whiskers as a high thermal conductivity phase to the matrix powder. The second slurry is made by adding 8 to 18 parts by weight of silicon carbide micro powder or boron carbide micro powder as a hard and wear-resistant reinforcing phase on the basis of the matrix powder.
7. The preparation method according to claim 6, characterized in that, The aluminum nitride whiskers have a length of 5–20 μm and a diameter of 0.5–2 μm; The average particle size of the silicon carbide micro powder or boron carbide micro powder is 0.5–2 μm; The sintering aid is composed of modified illite powder and polyvinyl alcohol modified ammonium alginate gel in a mass ratio of 1:0.5 to 2. In step S1, each slurry is placed in a ball mill and wet-milled at 200-400 rpm for 4-8 hours, and the solid content of the slurry is controlled at 40-60%.
8. The preparation method according to claim 5, characterized in that, In step S2: The core material layer accounts for 40-60% of the total mold volume, the surface wear-resistant layer accounts for 20-30% of the thickness, and the transition layer accounts for 20-30% of the thickness. During the grouting process, vibrations with a frequency of 20–50 Hz and an amplitude of 0.1–0.5 mm are applied to achieve in-situ composition gradient construction by utilizing the difference in settling rates of particles with different densities. The in-situ curing is performed by allowing the material to stand in a constant temperature and humidity environment for 2 to 6 hours. The drying process employs a gradient heating method: first, maintain the temperature at 60°C for 2 hours, then raise the temperature to 110°C and maintain it for 4 hours, and finally raise the temperature to 150°C and maintain it for 2 hours.
9. The preparation method according to claim 8, characterized in that... In step S3: The temperature is increased to 1500℃ at a rate of 5-10℃ / min and held for 1 hour; then the temperature is increased to 1750-1850℃ at a rate of 3-5℃ / min and sintered at 1-5MPa pressure for 2-4 hours. After sintering, the furnace is cooled to below 200°C before being removed from the furnace. The protective atmosphere is flowing nitrogen or argon.
10. The preparation method according to claim 9, characterized in that, If the ceramic column contains a reinforcing skeleton, the reinforcing skeleton is pre-positioned and fixed in the center area of the mold before slurry injection, and then slurry injection is performed so that the reinforcing skeleton is embedded inside the green body.
Citation Information
Patent Citations
Stock column under furnace of calcium carbide
CN204630383U
